2020
DOI: 10.1075/jsls.00014.liu
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic influence of L2 on L1 in late Chinese-English bilinguals

Abstract: Cross-linguistic influence studies usually investigate how the bilingual’s first language (L1) influences the acquisition and use of their second language (L2) within the L2 context. This study, by contrast, investigates how the bilingual’s L2 may influence their L1 within the L1 environment, specifically whether the L2 affects L1 performance in an L1 environment in Chinese (L1)-English (L2) late bilinguals, in the domain of subject realisation. Typologically, Chinese allows pronominal subjects to be optionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…However, only very few studies have considered bilinguals acquiring null-subject languages without rich inflection (e.g., Chinese, Korean, and Japanese: Chen and Lei (2012) on Chinese-English bilinguals, as discussed above; Blais et al (2010) on Japanese-French bilinguals). Liu et al (2020) confirmed the overproduction of subjects in Chinese-English bilinguals but the participants were late bilinguals. Kang (2013) investigated subject realization in Korean-English bilingual children but their strong dominance in Korean made the study less comparable with others in the current analysis.…”
Section: Crosslinguistic Influence (Cli) In Bilingual Children's Refe...supporting
confidence: 60%
“…However, only very few studies have considered bilinguals acquiring null-subject languages without rich inflection (e.g., Chinese, Korean, and Japanese: Chen and Lei (2012) on Chinese-English bilinguals, as discussed above; Blais et al (2010) on Japanese-French bilinguals). Liu et al (2020) confirmed the overproduction of subjects in Chinese-English bilinguals but the participants were late bilinguals. Kang (2013) investigated subject realization in Korean-English bilingual children but their strong dominance in Korean made the study less comparable with others in the current analysis.…”
Section: Crosslinguistic Influence (Cli) In Bilingual Children's Refe...supporting
confidence: 60%
“…The interface hypothesis further argues that syntactic structures located at the syntax-pragmatics interface are vulnerable to cross-linguistic influence, but not those that interface with semantics (Chamorro & Sorace, 2019). There is consistent evidence for cross-linguistic influence at the syntax-pragmatics interface Contemori et al, 2019;Ergün, 2021;Foryś-Nogala et al, 2020;Jachimek et al, 2022;Liu et al, 2020;Sopata, 2021;Sopata et al, 2021;Torregrossa et al, 2021;Van Dijk et al, 2022;Zhou et al, 2021). However, evidence for influence at the syntax-semantics interface is mixed (Bolonyai, 2007;Jachimek et al, 2022;Lebkuecher & Malt, 2021).…”
Section: L2 Influence On L1 Syntaxmentioning
confidence: 99%
“…Syntax-semantics interface, late bilingualism, cross-linguistic influence, Japanese, Korean First-language (L1) syntax was traditionally considered impervious to influence from a second language (L2; Chomsky, 1986;Schmid, 2011). However, there is mounting evidence for L2 influence on L1 syntax (Azaz & Frank, 2018;Ben-Rafael, 2004;Bosch & Unsworth, 2021;Dussias & Sagarra, 2007;Gürel, 2004;Lebkuecher & Malt, 2021;Liu et al, 2020;López Otero, 2022;Ramirez, 2003;Ribbert & Kuiken, 2010;Stolberg & Munch, 2010;Wolff & Ventura, 2009). A common explanation for these observations of L2 influence is that they reflect errors in retrieval rather than altered representation of syntax (Chamorro & Sorace, 2019;Schmid, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…e L1-L2 similarity (or congruence). Although cross-linguistic similarities do not always mean ease for L2 acquisition and differences do not necessarily cause difficulties, ample research has shown that some inter-linguistic differences, including those in functional morphology, pose serious challenges (Liu and Gleason, 2002;Liu et al, 2020;Montrul, 2001;Odlin, 1989). In other words, while complete congruence between learners' L1 and L2 can lead to positive L1 transfer, incongruence may often cause negative transfer, resulting in learning difficulties.…”
Section: Key Linguistic/input Variables Affecting the Acquisition Of ...mentioning
confidence: 99%